The position of a child offender under the laws of preventive detention in Malaysia /Sarirah Che Rose...[et al.] - Che Rose, Sarirah; Kamarudin, Irma (Universiti Teknologi MARA, Kedah, 2011)
Preventive detention is a detention order directed by the minister with a view to prevent a person from acting in any manner prejudicial to public order or because it is necessary for the suppression of violence or the prevention of crimes involving violence. When a person is detained under the laws of preventive detention, his/her right to be heard is deprived. That is why this kind of detention is also called a detention without trial. Any person, including a child is subjected to these laws if he or she goes beyond them. Even though there is a special Act namely, the Child Act 2001, it is not applicable in cases involving a child offender who is detained under the laws of preventive detention. Therefore, this paper discusses the reasons behind the judgment of the judges as to why the Child Act 2001 is not applicable in child offender cases. At the end of the discussion, the writers provide suggestions for the need of the applicability of the Child Act 2001 in child offender case.